New training load rating method in weightlifting - Kobyakov, Y. P.; Lovchev, A. V. (Theory and Practice of Physical Culture, 2018)
Objective of the study was to provide grounds for and develop a new training load rating method for weightlifting sport with application of energy costs in the International Physical Values Rating System (Systeme International d`Unitas, SI) i.e. in Joules (J) and kilo-Joules kJ.